Church and State patrimonial and royalty: The religious, economic and civil backgrounds in independence. Chile and beyond (1810-1830) - Cavieres Figueroa, Eduardo (2020)
This article deals with historical facts underlying the current secularization process including its relationships with modernity and liberalism. It also analyses part of the thought of a colonial family about the process, with an emphasis on its definition of «positive secularity». The main point focuses on State-Church discussion on power scopes.